PENGARUH AGLOMERASI, INVESTASI, DAN HUMAN CAPITAL TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Yuliara Elmariska; Sofyan Syahnur (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThe purpose of this study is to analyze the influence of agglomeration, investment and human capital of economic growth in Indonesia. The method used in this study is a quantitative analysis method using the Fixed Effect Model (FEM). The data used are panel data from 2010-2017. The data was obtained from the Badan Pusat Statistics Standard (BPS). Research shows that agglomeration have a positive but not significant impact on economic growth. Investments are positive and significant. Human capital has a negative and significant impact on economic growth in Indonesia.The results of this research are expected to be an encouragement for the government in making regulations relating to agglomeration in order to develop industrial areas evenly, investment to be more evenly distributed and human capital as a container to accommodate skilled workers, so that all three variables can contribute fully to economic growth in Indonesia.Keywords: Agglomeration, Investment, Human Capital, Economic Growth